Upaya Peningkatan Kemampuan Mengontrol Emosi Dengan Cara Fisik Pada Klien Resiko Perilaku Kekerasan Di Rsjd Dr. Arif Zainudin Surakarta - Nur Awaludin, Ikhsan, Arif Widodo, A.Kep., M.Kes (2016)
Background : Psychological health is not only having no mental disturbance, but is contains positive characteristic presenting psychological harmony and balance that is reflecting personality maturity. In 2012, figures with mental disorders is alarming globally. Approximately 450 milion people suffering from mental disorders. People who experience mental illnes third live in developing countries as many as 8 out of 10 people with mental disorders were not getting treatment. Purpose : Authors can understand nursing care in clients with violent behavior. Method : The method used is descriptive case study approach, is to perform nursing care in clients with violent behavior ranging from assessment, intervention, implementation and evaluation of nursing. Result : In this case found two diagnoses are injuring the selves, others and the environtment associated with violent behavior and the risk of violent behavior associated with low self esteem. Has been perfomed using a approach to violent behavior, after nursing care in getting the results the client is able to control anger or expressing angry with the way that the assertive. Conclusion : Cooperation between the health care team, adequate hospital facilities are needed to determine the success of the nursing care in the clien so that the client can implement ways to control violent behavior which has been given by nurses.